Innovative materials and techniques in concrete construction : ACES workshop - Fardis, Michael N. (Springer Netherlands, 2012)
Recent years have seen enormous advances in the technology of concrete as a material, through which its strength, compactness and ductility can reach levels never dreamed of before. Thanks to these improved material properties, the strength and durability of concrete structures is greatly improved, their weight and dimensions reduced, the scope of concrete as a structural material is widened and - despite the higher material costs - overall economy is possible, with positive impacts on sustainability as well. Similar advances are underway in reinforcing materials, notably high strength steel and fibre-reinforced polymers, and in the way they are combined with concrete into high performance structures. Developments in materials and equipment, as well as new concepts, have lead to innovative construction techniques, reducing cost and construction time and making possible the application of concrete under extreme conditions of construction or environment. All these advances will be highlighted in the book by the top experts in the field of concrete structures, namely those currently active in the field's leading and truly international scientific and technical association: the International Federation of Structural Concrete (fib) www.fib-international.org. Audience: Practicing engineers and firms, academics, researchers and graduate students, will all find the book timely, informative and very interesting.